Are less hierarchical firms organized around stronger cultures? Evidence from big data - Marchetti, Arianna; Puranam, Phanish (Strategic Management Journal, 2025)
Abstract Research Summary Are less hierarchical firms organized around stronger cultures instead? We analyze 1.5 million employee reviews on Glassdoor.com from 23,000 US‐based firms, alongside data on managerial hierarchy estimated from 42 million professional social media profiles. Our findings confirm a negative association between managerial hierarchy and organizational culture strength. We explore two potential explanations for this association: Functional equivalence between the two, and culture fragmentation caused by managerial hierarchy. Multiple correlational tests show support for functional equivalence as a plausible explanation for the observed negative correlation. Our findings enhance our understanding of the complex relationships between organizational structure and culture utilizing Big Data methods. Managerial Summary Can strong cultures, i.e., systems of widely shared beliefs and values converging on a few organizational dimensions, be an alternative to managerial hierarchy to align the work of employees? Our analysis of 1.5 million Glassdoor employee reviews and 42 million professional profiles from 23,000 U.S. firms shows that organizations with stronger cultures do indeed have a lower fraction of managers to total employees. This suggests that attempts to “flatten” hierarchies by eliminating layers of managers is more likely to succeed if accompanied by efforts to build strong cultures, through mechanisms such as careful selection and socialization of workers.